Thermal process of castor and plant based oil - Ahmad, Mohammad Haniff; Ibrahim, Wan Asma; Sazali, Jahirah; Izhab, Izirwan; Zulkafli, Hassan (Department of Chemistry, Universitas Gadjah Mada Yogyakarta, 2020)
Castor oil is an oil derived from castor seed from a plant Ricinus communis. The versatility of castor oil is highly attributed by 12-hydroxy-9-octadecenoic acid (ricinoleic acid) and its functional group. It is an oil that cannot be consumed by a human. However, castor oil actually can be used to produce many valuable products such as chemicals, paint, and cosmetics due to its unique characteristic which contains a high percentage of ricinoleic acid that helps in producing many valuable products. The utilization of vegetable oils is currently in the highlight of the chemical industry, as they are one of the most important renewable resources due to their universal availability, inherent biodegradability, low price, and eco-friendly. Therefore, the main aim of this paper is to focus on the thermal cracking of castor oil with Zeolite ZSM-5 as the catalyst generates products consisting alcohol, methyl esters and fatty acids which are valuable raw materials for industries. The background, characteristics, composition, properties and industrial application of castor oil have also been discussed. The important properties and various applications of castor oil which can be obtained from toxic seeds have much greater potential than other available vegetable oils.